Investigating the Tenor Continua in Femi Osofisan’s Women of Owu through the Hallidayan Mood Grammar - AMOUSSOU, CELESTIN YEMALO; ASSOGBA, Judes (My University, 2020)
This paper analyses the Mood structure and system in two extracts from the Nigerian playwright Femi Osofisan‟s (2006) The Women of Owu with a view to decoding the role relationships established among war winners and losers. Drawing on the SFL requirements for text analysis, researchers have first identified, categorized, quantified, analyzed and interpreted the language data related to the three components of the grammar of interpersonal meaning, namely mood, modality and adjunct types selected by different participants in the conversations to assert the three tenor continua: power, contact and affective involvement. The findings reveal that though contract is frequent among the interactants, the affective involvement among them is low and the power unequal.
Keywords: mood; modality; adjunct; interpersonal relationship.